The Role Of The University In Developing The Rural Community- A Study On The Impact Of Social Sciences On Rural Society - Benkbi , Amina; Hellab , hakim (Journal of Social Sciences and Humanities, 2023)
This empirical study tackles the role of the university to develop the rural community throughout teaching and educating students the different techniques of sciences. Therefore, those students will contribute to transfer the acquired knowledge and use it in their real life situations across their different living districts. Accordingly , the Algerian university , like other universities , has performed its historical role in contributing to free the Algerian citizen, protecting his history , preserving his different values and promoting his language by imposing its use in all the fields of life where the social sciences play an important role in developing the identity , preserving the privacy , achieving the social cohesion and the mental health of the Algerian society , besides its integration , collaboration , stability and tranquility . This is because all the branches of the social knowledge complement and support each other.